Hypo-Expression of Flice-Inhibitory Protein and Activation of the Caspase-8 Apoptotic Pathways in the Death-Inducing Signaling Complex Due to Ischemia Induced by the Compression of the Asphyxiogenic Tool on the Skin in Hanging Cases - Maiese, Aniello (Diagnostics (Basel), 2020)
The FLICE-inhibitory protein (c-FLIPL) (55 kDa) is expressed in numerous tissues and most abundantly in the kidney, skeletal muscles and heart. The c-FLIPL has a region of homology with caspase-8 at the carboxy-terminal end which allows the molecule to assume a tertiary structure similar to that of caspases-8 and -10. Consequently, c-FLIPL acts as a negative inhibitor of caspase-8, preventing the processing and subsequent release of the pro-apoptotic molecule active form. The c-FLIP plays as an inhibitor of apoptosis induced by a variety of agents, such as tumor necrosis factor (TNF), T cell receptor (TCR), TNF-related apoptosis inducing ligand (TRAIL), Fas and death receptor (DR). Increased expression of c-FLIP has been found in many human malignancies and shown to be involved in resistance to CD95/Fas and TRAIL receptor-induced apoptosis. We wanted to verify an investigative protocol using FLIP to make a differential diagnosis between skin sulcus with vitality or non-vital skin sulcus in hanged subjects and those undergoing simulated hanging (suspension of the victim after murder). The study group consisted of 21 cases who died from suicidal hanging. The control group consisted of traumatic or natural deaths, while a third group consisted of simulated hanging cases. The reactions to the Anti-FLIP Antibody (Abcam clone-8421) was scored for each section with a semi-quantitative method by means of microscopic observation carried out with confocal microscopy and three-dimensional reconstruction. The results obtained allow us to state that the skin reaction to the FLIP is extremely clear and precise, allowing a diagnosis of unequivocal vitality and a very objective differentiation with the post-mortal skin sulcus.